The Impact of Thrown Ball Drill and Deep Drive Training on Backhand Hitting Ability of Field Tennis Players - Fauzan, Lazuardy Akbar; Rahmadi, Rahmadi; Ndayisenga, Japhet; Haïdara, Youssouf; Németh, Zsolt (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. Backhand shots really need to be mastered well by field tennis players. Mastery of quality backhand shot techniques will affect player motivation in the match. The purpose of this study was to determine the effect of thrown ball drill training on the results of backhand shots. Materials and methods. The research method used is experimental. The treatment in this study was 16 training sessions. This research was conducted on 16 JPOK ULM tennis players. This study used total sampling technique. To collect backhand data, this study used the Hewitt Tennis Achievement Test instrument. This study used a t-test to analyze the data by looking at the increase in pre-test and post-test scores. Results. The results of this study resulted in thrown ball drill training and deep drive training being able to improve the ability of JPOK ULM tennis players' backhand shots. this research obtained thrown ball drill training obtained t-count more than t-table 2.365 < 17.60. Deep drive training obtained t-count more than t-table 2,365 < 8.05. Conclusion. Thrown ball drill and deep drive training methods can be applied to train tennis players' backhand shots. Thrown ball drill training has more effect on improving the backhand ability of JPOK ULM student tennis players.